A study on criminal deportation; prepared for the Ministry of National Security and the Planning Institute of Jamaica - Barnes, Annmarie ([s.n.] [S.l.], 2006)
Examines the impact of criminal deportation on crime in Jamaica. Evaluates the implications for national security